Digital cinema - Prince, Stephen, 1955-2020 (Quick takes., 2019)
Digital Cinema considers how new technologies have revolutionized the medium, while investigating the continuities that might remain from filmmaking's analog era. In the process, it raises provocative questions about the status of realism in a pixel-generated digital medium whose scenes often defy the laws of physics. It also considers what these changes might bode for the future of cinema. How will digital works be preserved and shared? And will the emergence of virtual reality finally consign cinema to obsolescence? Stephen Prince offers a clear, concise account of how digital cinema both extends longstanding traditions of filmmaking and challenges some fundamental assumptions about film. It is essential reading for anyone interested in understanding how movies are shot, produced, distributed, and consumed in the twenty-first century.